Traffic Flow Detection Using Distributed Fiber Optic Acoustic Sensing - Huiyong Liu; Jihui Ma; Wenfa Yan; Wensheng Liu; Xi Zhang; Congcong Li (IEEE Access)
This paper proposes a novel method for traffic flow detection using distributed optical fiber acoustic sensing (DAS). Different from the traditional traffic flow detection method, this method detects the traffic vibration signal using a fiber optic cable. Distributed fiber-optic acoustic sensing technology can provide fully distributed acoustic information along the entire fiber link, and thus external acoustic signals from an arbitrary point can be detected and located. This paper uses DAS to obtain traffic vibration data. Using the characteristics of traffic vibration data, this paper proposes an improved wavelet threshold algorithm and an improved dual-threshold algorithm and verifies the feasibility and effectiveness of these methods. Finally, the experimental results from a vehicle-counting test show that the counting error is smaller for a single vehicle passing through the detection area and that the counting error is larger if multiple vehicles pass through the detection area continuously. In vehicle speed estimation, the results show good accuracy, and the error range is controlled to less than 6%.